Princess Mononoke - Mononoke-hime - Hayao Miyazaki (1997)
Claire Danes, Minnie Driver and Billy Bob Thorton head a cast of hot Hollywood stars who lend their talents to this exquisitely animated, overwhelmingly acclaimed adventure epic! Inflicted with a deadly curse, a young warrior named Ashitaka sets out to the forests of the west in search of the cure that will save his life. Once there, he becomes inextricably entangled in a bitter battle that matches Lady Eboshi and a proud clan of humans against the forest's animal gods... who are lead by the brave Princess Mononoke, a young woman raised by wolves! Also starring Gillian Anderson and Jada Pinkett Smith, this monumental struggle between man and nature will have you transfixed with amazement as stunning artistry blend with epic storytelling to create a uniquely entertaining motion picture! Languages: English, French, Japanese
Keywords: Animation, Adventure, Fantasy